Pengembangan Media Pembelajaran Uang Kertas Berbantu Huruf Braille Untuk Memfasilitasi Pengetahuan Sosial Finansial Individu Dengan Hambatan Penglihatan (Penelitian Pengembangan Pada Pendidikan Inklusi Di Kota Tasikmalaya) - Syifa Azkia Purwanti; Sima Mulyadi; Edi Hendri Mulyana (JURNAL PAUD AGAPEDIA, 2023)
Social financial knowledge is knowledge related to finance in everyday life that is important for every individual from all walks of life, including persons with disabilities, one of whom is an individual with visual impairments. Based on a preliminary study on 5 special schools in Tasikmalaya City, the socio-financial knowledge of individuals with visual impairments is still low. This is shown by the students not being able to recognize and distinguish nominal banknotes. The low socio-financial knowledge of individuals with visual impairments is caused by the absence of appropriate specific learning media for students to be able to recognize and distinguish nominal money through their physical characteristics. This research aims to develop learning media that is capable of facilitating the socio-financial knowledge of individuals with visual impairments in recognizing and distinguishing banknote denominations. The research subjects consisted of sixteen individuals with visual impairments. The research method used is Design Based Research (DBR) which consists of four research stages, namely: 1) problem identification and analysis; 2) prototype solution design; 3) repeated cycles in testing and improving the design; 4) reflection to generate design principles and implementation. The data collection technique used was interviews with teachers and tests on individuals with visual impairments. Learning media has gone through the stages of expert validation and user validation. The results of the product were declared fit for use to facilitate social-financial knowledge of individuals with visual impairments in recognizing and distinguishing banknote denominations. Pengetahuan sosial finansial adalah pengetahuan yang berkaitan dengan keuangan dalam kehidupan sehari-hari yang penting dimiliki oleh setiap individu dari berbagai kalangan termasuk penyandang disabilitas, salah satunya individu dengan hambatan penglihatan. Berdasarkan studi pendahuluan pada 5 SLB di Kota Tasikmalaya, pengetahuan sosial finansial individu dengan hambatan penglihatan masih rendah. Hal tersebut ditunjukkan dengan peserta didik belum mampu mengenal dan membedakan nominal uang kertas. Rendahnya pengetahuan sosial finansial individu dengan hambatan penglihatan disebabkan belum adanya media pembelajaran khusus yang tepat untuk peserta didik dapat mengenal dan membedakan nominal uang melalui ciri fisiknya. Penelitian ini bertujuan mengembangkan media pembelajaran yang mampu memfasilitasi pengetahuan sosial finansial individu dengan hambatan penglihatan dalam mengenali dan membedakan nominal uang kertas. Subjek penelitian terdiri dari enam belas individu dengan hambatan penglihatan. Metode penelitian yang digunakan adalah Design Based Research (DBR) yang terdiri dari empat tahap penelitian, yakni: 1) identifikasi dan analisis masalah; 2) perancangan prototype solusi; 3) siklus berulang dalam pengujian dan penyempurnaan rancangan; 4) refleksi untuk menghasilkan prinsip-prinsip desain dan implementasi. Teknik pengumpulan data yang digunakan adalah wawancara pada guru dan tes pada individu dengan hambatan penglihatan. Media pembelajaran telah melalui tahap validasi ahli dan validasi pengguna. Hasil produk dinyatakan layak digunakan untuk memfasilitasi pengetahuan sosial finansial individu dengan hambatan penglihatan dalam mengenal dan membedakan nominal uang kertas.